Translocation of Nitrate in Rice Rhizosphere and Total Nitrogen Uptake Improvement under Interactive Effect of Water and Nitrogen Supply. Issue 3 (4th February 2023) - Rushimisha, Iranzi Emile; Wang, Weimu; Li, Yongtao; Li, Xiaojing
ABSTRACT: Nitrogen, an essential macronutrient for rice ( Oryza sativa L ), mineral forms are extremely prone to leaching. In this study, pot experiment in a greenhouse was utilized to investigate the coupling effect of irrigation (W) and fertilizer (N) on nitrate (NO3 -N) translocation in the soil-water-plant system, Total Nitrogen (TN) uptake. Three N levels (Low, Medium, High: N1, N2, N3 ) rated 25, 120, and 250 mg/kg similarly three W levels (Low, Medium, High: W1, W2, W3 ) 70%-80%, 80%-90% and 100% of field capacity (θf) +0.5 cm submergence depth were applied. Nine treatments (W1 N1 :T1, W1 N2 :T2, W1 N3 :T3, W2 N1 :T4, W2 N2 :T5, W2 N3 :T6, W3 N1 :T7, W3 N2 :T8 and W3 N3 :T9) with four replicates. To understand NO3 -N distribution, six soil layers (1 cm width each) per treatment were generated making it 54 in total. T6 (69.2%) revealed the highest increment in NO3 -N content followed by T7 (44.2%) and T8 (39%) compared to T1. Generally, Middle layers (3 rd -4 th ) had the least NO3 -N content compared to shallow (1 st -2 nd ) and bottom (5 th -6 th ) layers. Concerning TN, the highest was found in T3(63%), T2(45%) and T6(41.5%) and T7(-26%) with the highest decrement. Interacting W and N significantly affected means of NO3 -N, TN, moisture content, and root shoot ratio (R/S) at 5% probability level. Results of this study suggested that proper W and N combination result in high rhizosphere NO3 -N accumulation in shallow layers leading to high nitrogen uptake by plant thus N leaching reduction.